Building healthy foundations: Screening for 4 D's (defects at birth, diseases, deficiencies, and development delays) among under-five children under the Rashtriya Bal Swasthya Karyakram program in Bengaluru, South India - R. Deepthi; Ameenah Anwar Hussain Siraja; Gokul Santhosh; M Vinaya (Wolters Kluwer Medknow Publications, 2024)
Introduction: The 1st 2000 days of a child's life from conception to five years of age are the most crucial days for early childhood development. The Rashtriya Bal Swasthya Karyakram (RBSK) is an ongoing screening screening program aims to screen the children not only in these crucial years but until they are 18 years of age and routinely refers them to higher centers for further management. Our study aimed to determine the 4 Ds - defects, deficiency, disease, and disability for children under five years of age, screened under RBSK. Methods: A cross-sectional study was conducted in one rural and two urban Primary Health Centers (PHCs) under the field practice area of government medical college in Bengaluru, South India. All the children registered under the anganawadi centers of the selected PHCs were included. Anthropometric measurements including weight, height, and mid upper-arm circumference were collected. Data was also collected from RBSK reports. Results: Among the 760 children screened, 41.6% deficiencies, 2.6% childhood diseases, and 0.3% disabilities and zero (0) defects were detected. Conclusion: The reporting of deficiencies was substantial (41.6%) under the RBSK program. But, the reporting of developmental delay and defects was not regular and was very low. To enhance its effectiveness, strategies include improving infrastructure and resources, strengthening screening and early detection through trained health-care workers, and standardized tools. Capacity building and training for health-care professionals are essential, as is community engagement through awareness campaigns and collaboration with local organizations.